Willingness to receive COVID‐19 booster dose and its associated factors in Ghana: A cross‐sectional study - Rebecca Peniel Storph; Mainprice Akuoko Essuman; Ruth Duku‐Takyi; Albert Akotua; Samuel Asante; Richard Armah; Irene Esi Donkoh; Prince Anim Addo (Health Science Reports, 2023)
Abstract Background and Aim The COVID‐19 booster dose has been cited as an important supplement for the control of the COVID‐19 pandemic due to reports of waning immunity among fully vaccinated persons. Determining factors that would affect its acceptability is necessary for initiating successful vaccination programs. In this study, we aimed to evaluate the factors associated with the acceptability of the COVID‐19 booster dose in Ghana. Methods We conducted an online cross‐sectional survey among the public. A self‐administered questionnaire was used to collect information on demographic characteristics, willingness to vaccinate, perceptions toward COVID‐19 vaccines, and trust in the government. Participants provided reasons and sources of advice that may affect their willingness to accept a booster dose. Using IBM SPSS and R Statistic; descriptive, univariate, and multivariate analyses were performed. Results Out of 812 respondents, 375 (46.2%) intended to accept the booster dose. Individuals who were males (adjusted odds ratio [aOR] 1.63, 95% confidence interval [CI] 1.07−2.48), had previously received other forms of vaccination twice (aOR 1.96, 95% CI 1.07−3.57) or in most years (aOR 2.51, 95% CI 1.38−4.57), tested positive for COVID‐19 (aOR 3.46, 95% CI 1.23−10.52), have high trust in government (aOR=1.77, 95% CI: 1.15‐2.74) and had positive perceptions regarding COVID‐19 vaccines (OR = 14.24, 95% CI: 9.28−22.44) were more likely to accept a booster dose. Experiencing side effects from the primer dose (aOR 0.12, 95% CI 0.08−0.18) was associated with reduced acceptance. Concerns about vaccine safety and efficacy were the common reasons impeding willingness, while advice from health professionals would be the most considered. Conclusion Low intention to accept the booster dose which is associated with a range of factors including the perception of vaccines and trust in the government, is a cause for concern. Thus, more effort would have to be taken through education and policy interventions to increase booster vaccine acceptability.